Leksem "słowo" w powieściach bałkańskich Teodora Tomasza Jeża = Lexem "word" in the Balkan novels of Teodor Tomasz Jeż - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is devoted to the use of the word "word" in the Balkan novels of T.T. Jeż. The analysis showed that the writer used the analyzed unit rather in traditional meanings, which are recorded in lexicographic sources. Also, the inflectional forms of the analyzed unit observed in the studied texts do not differ from the ways in which individual cases are used in Polish.
Keywords: Jeż, Teodor Tomasz (1824-1915); powieści bałkańskie; leksem słowo; znaczenie wyrazu; postaci fleksyjne wyrazu; kolokacje; Balkan novels; lexeme word; meaning of the word; inflectional forms of words; collocations